Perencanaan Karir dalam Pendidikan Islam (Studi Literatur) - Aprima, Septi Gia; Jamilus, Jamilus (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Islamic education. The research approach used is qualitative with a literature study method. The main source of research data is research articles published through various journals and indexed by google scholar. Data collection was carried out using the keyword